SURVIVAL AND ANGIOGRAPHIC RESULTS AFTER ENDARTERECTOMY FROM THE LEFT ANTERIOR DESCENDING ARTERY - A. P. Bogdan; S. A. Belash; K. O. Barbukhatti (Российский кардиологический журнал, 2014)
Aim. To assess optimal tactics of treatment of the patients wth diffuse atherosclerotic lesions of left anterior descending artery (LAD).Material and methods. The results of 320 patients studied, of those 149 underwent endarterectomy (EAE) from LAD (the EAE group), and CABG group consisted of 103 patients with locally-proximal type of coronary arteries involvement, therapy group — 68 patients, who were refused from surgical treatment due to serious changes of distal part of the arteries. Mean age, gender and concomitant pathology did not significantly differ. All operations were done under the artificial circulation conditions. In 100% cases for LAD revascularization arteria thoracica interna was used. Patients without surgical treatment were recommended optimal drug treatment. In follow-up period 127 EAE patients studied, 99 — CABG group, 58 — drug treatment group. Mean period of follow-up was 43,3±23,9 months.Results. Survival after CABG with EAE from LAD was 89,3% (95% confidence interval (CI) 83,9 to 94,1%). This value for the patients with diffuse atherosclerotic LAD defect, only on drug therapy, was 70,7% (95% CI 60,9-80,5%), (p=0,038). The death causes in the surgical group were progression of concomitant noncardiovascular pathology. Mortality of patients on drug therapy was related to cardial pathology. MI during the period was in 3 patients from EAE group and 5 patients from drug therapy group. Absence of angina was in 95,7% patients from EAE group and 93,5% in CABG. By the data of control coronary bypass graphy, the functioning of the grafts to the arteries after EAE in long-term follow-up did not statistically significantly differ from CABG group.Conclusion. The CABG results with EAE are nearly same as of CABG only and provide satisfactory survival and life quality in long-term follow-up. CABG with EAE in those with diffuse distal LAD atherosclerosis provides better prognosis and life quality comparing to conservative therapy and can be recommended for the treatment of these patients.